Fabrication and characterization of silk fibroin-derived curcumin nanoparticles for cancer therapy - Gupta, Vishal (Dove Medical Press, 2009)
Biologically derived nanoparticles (<100 nm) were fabricated for local and sustained therapeutic curcumin delivery to cancer cells. Silk fibroin (SF) and chitosan (CS) polymers were blended noncovalently to encapsulate curcumin in various proportions of SF and CS (75:25, 50:50, and 25:75 SF:CS) or pure SF at two concentrations (0.1% w/v and 10% w/v) using the devised capillary-microdot technique. Curcumin-polymer conjugates were frozen, lyophilized, crystallized, suspended in phosphate-buffered saline for characterization, and tested for efficacy against breast cancer cells. All nanoparticle formulations except 0.1% w/v 50:50 SFCS were less than 100 nm in size as determined with the transmission electron microscopy. The entrapment and release of curcumin over eight days was highest for SF-derived nanoparticles as compared to all SFCS blends. The uptake and efficacy of SF-coated curcumin was significantly higher (p < 0.001) than SFCS-coated curcumin in both low and high Her2/neu expressing breast cancer cells. Interestingly, the uptake of curcumin was highest for the high Her2/neu expressing breast cancer cells when delivered with a 10% w/v SF coating as compared to other formulations. In conclusion, SF-derived curcumin nanoparticles show higher efficacy against breast cancer cells and have the potential to treat in vivo breast tumors by local, sustained, and long-term therapeutic delivery as a biodegradable system.